History of the Ottawa and Chippewa Indians of Michigan - Blackbird, Andrew J., approximately 1820-1908 (Andrews UK, 2012)
"History of the Ottawa and Chippewa Indians of Michigan, a grammar of their language, and personal and family history of the author"--Page 1.